"It is a very difficult process": career service providers' perspective on career counseling in Pakistani universities. Issue 1 (January 2022) - Keshf, Zehra; Khanum, Saeeda
Abstract: Career guidance and counseling (CGC) is needed by many university students in Pakistan. Career service providers (CSPs) can offer appropriate services if they have a sound understanding of CGC needs of students. This study explores perspectives of CSPs working in Pakistani universities about career needs of their students, services offered to their students and the challenges encountered in this process. Qualitative semi-structured interviews with seven CSPs working in two major cities of Pakistan were carried out. Thematic analysis revealed variety of needs (like self-awareness, decision making), services (like one to one counseling, career fairs, seminars) and multiple challenges (like unrealistic expectations of students, insufficient resources) regarding CGC. Results are discussed along with thematic maps. Research implies that CSPs could expand and promote their services; CGC could be customized as per local community needs; parental concerns could be dealt with CGC; CGC could be aligned with academia as well as industry. Future research could look into planning, execution, impact and comparisons of indigenous CGC services. Abstract : Career counseling; Career needs; Career services; Qualitative; Students.